The effectiveness of the developed Nardo model in acquiring philosophical concepts among fifth grade literary students - Allawi, Muhammad Ahmed; Ahmed, Ahmed Bassem (Journal of Tikrit University for Humanities, 2024)
Roman, two researchers, through their current research, identify “the effect of the developed Nardo model on the acquisition of philosophical concepts among fifth grade literary students.” The research was conducted among the students of the fifth literary grade, as the students of the experimental and control groups were identified. The number of students reached (72) students, distributed into two monthly groups and another control group. The first experimental group was administered according to the developed Nardo model and consisted of (35) students. The control group was approved for the success of the regular method, and consisted of: (37) students. Experimental and control equivalence has been done in a number of properties, including (age, previous achievement test, intelligence), and the specialization has been prepared not according to the developed Nardo model, and the judicial plans lag behind the ordinary, and after several require philosophical concepts. The research reached the following result:- Nardo's developed model for literary fifth students helps students acquire philosophical concepts and suggests the researcher who wants other models of constructivism for beginners.